2014
DOI: 10.29173/cmplct22978
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Educational Leadership: The Emergence of Human Interactional Sense-Making Process as a Complex System

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
6
0
4
Order By: Relevance
“…Collective leadership: Turbulent realities and constant changes are so demanding in educational contexts that it is no longer possible for individuals to exercise leadership on their own (Jäppinen 2014;Weick and Sutcliffe 2007). Indeed, our findings imply that the era of individually-based leadership is over.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective leadership: Turbulent realities and constant changes are so demanding in educational contexts that it is no longer possible for individuals to exercise leadership on their own (Jäppinen 2014;Weick and Sutcliffe 2007). Indeed, our findings imply that the era of individually-based leadership is over.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, in the present chapter, we shall contribute to discussion on reforming teacher education by focusing on leadership practices in one Finnish teacher education department which has successfully transformed its practices. Conducted within the framework of a subject-centered socio-cultural approach (Eteläpelto et al 2013;2014), the study reported here elaborated pitfalls and insights applicable to moving teacher education in a more innovative and collaborative direction. The focus was on a group of four teacher education leaders who were striving to build shared leadership practices, and thus to develop teacher education practices and culture.…”
Section: Introduction: Importance Of Leadership In Teacher Educationmentioning
confidence: 99%
“…Eğitim yöneticileri, Çanakkale İl Milli Eğitim Müdürlüğünde risklerin etkili yönetilmesi, dönüşüm veya oluşum için ölçüte dayalı personel seçiminin ve ölçüte dayalı bir performans değerlendirme ve ödüllendirme sisteminin uygulanması için her fırsatta üst makamlara görüşlerini ilettikleri anlaşılmaktadır. Nitekim Jäppinen (2014), eğitim örgütlerinin sosyal bir sistem olarak holistik bir bakış açısıyla ele alınmasını ve oluşum sürecinde takım halinde karar vermenin önemli olduğunu ortaya koymaktadır.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Şöyle ki liderlik, değerleri eyleme, vizyonları gerçekliğe, engelleri yeniliklere, ayrılıkları dayanışmaya ve riskleri ödüllere dönüştürme süreci olarak görülmektedir. Bu nedenle liderler, önemli başarıların elde edilmesi için fırsatlar ve örgüt içinde uygun iklimler yaratan kişilerdir (Kouzes & Posner, 2012, s.2 bilimlerinde araştırıldığı yapılmış çok sayıda çalışma (Da'as, Schechter & Qadach, 2018;Fenwick, 2009;Fidan & Balcı, 2017;Gilstrap, 2005;Jäppinen, 2014;Marion & Uhl-Bien, 2001;McClellan, 2010;Ng, 2013;Osberg, 2005;Osborn & Hunt, 2007;Schneider & Somers, 2006;Svyantek & Brown, 2000) bulunmaktadır. En basit şekliyle karmaşıklık kuramı, fiziksel ve sosyal olguları basit nedensonuç ilişkisiyle açıklayan, linear (doğrusal) ve mekânistik dünya görüşüne karşıdır.…”
Section: Introductionunclassified
“…In recent years, especially, research has been conducted about what school leaders do or how they look upon and describe their practice (Carraway & Young, 2015;Coburn, 2005;Jäppinen, 2014;Morison, 2010;Nilsson, 2015;Rigby, 2015). Our article forms one contribution to understanding how leaders interpret the assignment and the chances and conditions of doing a good job, within process and practice-based research.…”
Section: Introductionmentioning
confidence: 98%